Organizing State and Local Health Departments for Public Health Preparedness - Wasserman, Jeffrey (RAND Corporation, 2006)
Explains the factors influencing the particular ways in which state and local public health systems are organized, how the various types of relationships that exist between state and local public health departments have been arrived at, and, most important, the consequences of such structures and relationships for emergency preparedness.